Dampak Riil Penghindaran Pajak Pada Perusahaan Manufaktur di Bursa Efek Indonesia - Wardani, Dewi Kusuma (Universitas PGRI Yogyakarta, 2020)
This study aims to examine the effect of tax avoidance to firm value, cost of capital, cash holding, capital structure. This sample used is a manufacturing companies during the year 2013-2017, based on the method of purposive sampling obtained 43 manufacturing companies. The stastical method used in this study was simple regression. This research results indicate that tax avoidance does not effect on the firm value, cash holding, and capital cost. Â Tax avoidance have a negative effect on the capital structure. Â Keywords: Firm Value, Cost of Capital, Cash holding, Capital Structure, Tax Avoidance.